Pediatric firearm mortality in the United States, 2010 to 2016: A National Trauma Data Bank analysis. Issue 3 (March 2020) - Hatchimonji, Justin S.; Swendiman, Robert A.; Goldshore, Matthew A.; Blinman, Thane A.; Nance, Michael L.; Allukian, Myron; Nace, Gary W.
Abstract : BACKGROUND: Pediatric firearm injury is a leading cause of death for U.S. children. We sought to further characterize children who die from these injuries using a validated national database. METHODS: The National Trauma Data Bank 2010 to 2016 was queried for patients aged 0 to 19 years old. International Classification of Diseases external cause of injury codes were used to classify patients by intent. Differences between groups were analyzed using χ 2 or Mann-Whitney U tests. Patterns over time were analyzed using nonparametric tests for trend. Multivariable logistic regression was used to investigate associations between the above factors and mortality. RESULTS: There were a total of 45, 288 children with firearm injuries, 12.0% (n = 5, 412) of whom died. Those who died were younger and more often white than survivors. Mortality was associated with increased injury severity, shock on presentation, and polytrauma ( p < 0.001 for all). There was an increasing trend in the proportion of self-inflicted injuries over the study period ( p < 0.001), and mortality from these self-inflicted injuries increased concordantly (35.3% in 2010 to 47.8% in 2016, p = 0.001). Location of severe injuries had significant different mortality rates, ranging from 51.3% of head injuries to 3.9% in the extremities. In the multivariable model, treatment at a pediatric trauma center was protective against mortality, with odds ratios of 2.10 (confidence interval, 1.64–2.68) and 1.80 (confidence interval, 1.39–2.32) for death at adult and dual-designated trauma centers, respectively. This finding was confirmed in age-stratified cohorts. CONCLUSION: Proportions of self-inflicted pediatric firearm injury in the National Trauma Data Bank increased from 2010 to 2016, as did mortality from self-inflicted injury. Because mortality is highest in this subpopulation, prevention and treatment efforts should be prioritized in this group of firearm-injured children. LEVEL OF EVIDENCE: Epidemiological study, level V. Abstract : Supplemental digital content is available in the text.